NILAI-NILAI PENDIDIKAN DALAM SENI TUTUR BEGALAN DIBANYUMAS - Wien Pudji Priyanto (Jurnal Cakrawala Pendidikan, 2008)
Banyumas, as a region in Central JavaProvince~ is geographically locatedbetween two different ethnic groups, namely the Javaneseand the Sundanese. Thismakes Banyumas receive influences from two different culturesand have specificand unique characteristics. Banyumas has a variety ofarts such as, among others,lengger calung, ebeg, baritan, buncisan, angguk, wayang kulit gagrag Banyumas,aksimuda, cowongan, laisan, ·aplang/dhaeng, karawitan, ujungan dan Seni tutur Begalan.Seni Tutur Begalan is one religious or ritual art because it is performed in a specifictraditional wedding ·ceremony in Banyumas. The marriage is specific when it isbetweenthe eldest daughter and the eldest son, the youngest daughter and theyoungest son, the eldest daughter·and the youngest son, and the youngestdaughterand the eldest son. Educational values ·in seni tutur Begalan include,among others, the following;(1) religious values can be found in a variety ofcomponents in the offering .preparedfor the Begalan ceremony, reflecting therelationship between people and good, people and the nature, and people andpeople (habluminallah-habluminannas); (2). social values can be found in the advice orsayings throughpikulan (Brenong Kepang), suggesting a value that serious or trivialproblems canbe solved together; (3) moral values are presented through the lyricsof tembang eling-eling, reflecting three important points, namely tata krama(politeness), temen (seriousness), and .tepa selira.(tolerance), which are important insocial life